ONOMATOPE DALAM KOMIK MILES MORALES: SPIDER-MAN 2019 - Lingga Julinafta; Retno Purwani Sari (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
The study investigates onomatopoeia in all of its forms and meanings as seen in the digital comic